HUBUNGAN INTELLECTUAL CAPITAL, CORPORATE SOCIAL RESPONSIBILTY DAN CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN - Setiyowati, Supami Wahyu; Mardiana, Mardiana (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2020)
Financial performance is an achievement obtained by companies, especially in the financial statements contained in financial reports for a certain period. The purpose of this study is to determine the relationship between intellectual corporate social responsibility (CSR) and corporate governance (CG) on financial performance in Islamic banking companies. This research is a quantitative research. Using purposive sampling. The population of Islamic banking companies is on the Indonesia Stock Exchange for the period 2014-2018. The sample is 6 Islamic banking companies. The data analysis technique uses multiple regression. The results showed that simultaneously and partially intellectual capital, corporate social responsibility, and corporate governance influenced financial performance. The conclusion is that the higher the intellectual capital, the higher the financial performance. The increased disclosure of corporate social responsibility shows an increase in financial performance. Implementation of corporate governance improves financial performance. Advice for investors and potential investors to see an increase in intellectual capital, disclosure of corporate social responsibility and corporate governance before investing to see the company's overall performance to benefit